Cybersecurity Risks in E-Banking: An Analysis of Consumer Perceptions, Intentions, and Industry Response in Qatar - Taha, Mahitab (2021)
This thesis regards the impact of new technologies in the banking industry, mainly in Qatar, and more precisely the attitudes of retail clients toward the technology in their day to day transactions. One may anticipate advantages for consumers in having the capabilities to initiate transactions by virtual means, yet those same clients may be reluctant to utilize these channels due to higher cyber risks. The objective of this study was to analyze these attitudes through an appropriate survey measurement, and to determine how a retail bank may optimize its business model to preserve the trust of its clients. Perceived confidentiality, integrity, and availability were found to have a significant effect on perceived security and overall perceived risk, which in turn had a negative effect on e-banking use; while government regulations were found to have a partial positive effect on e-banking acceptance.